FORMATION OF PROFESSIONAL COMPETENCES OF STUDENTS OF THE TRAINING DIRECTION "ADAPTIVE PHYSICAL CULTURE" IN THE FRAMEWORK OF THE PROJECT "SCHOOL OF HEALTH FOR CHILDREN WITH MENTAL DISABILITIES" - Pravdov, M.A.; Mikhailov, A.A.; Chirkin, N.A.; Buslovskaya, L.K. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the degree of formation of professional competencies among students of the direction of training adaptive physical culture in the process of implementing the project "School of Health for Children with Mental Disabilities". Methods and structure of the study. During the implementation of the project "School of Health for Children with Mental Disabilities "Expand Boundaries" it was attended by 100 children with mental disabilities from boarding schools in the Ivanovo region, 40 students and 19 teachers of the Shuya branch of the Ivanovo State University. Experimental (EG) and control (CG) groups of 20 people were formed from among the students. In the process of implementing the project, two groups of tasks were solved: to form professional competencies among students enrolled in the educational program "Physical rehabilitation in the direction of training 49.03.02 Physical culture for people with disabilities (adaptive physical culture)", for the organization and conduct of various forms physical culture and health-improving and sports activities with children with mental disorders; creation of an educational environment that ensures the availability of quality education and successful socialization for people with disabilities. Results and conclusions. During the pedagogical experiment, APC students got the opportunity to effectively develop professional competencies, personal growth, and creativity. It was noted that students from the EG had a qualitatively increased degree of professional competencies in comparison with students from the CG.